Psychiatry and Sports Medicine - Imboden C; Claussen MC; 2; 3; Seifritz E (Dynamic Media Sales Verlag, 2021)
Aim: We conducted an umbrella review of 55 meta-analyses to summarize current evidence on the effects of exercise on depression.Results: Aerobic, resistance or combined exercise for several weeks as well as mind-body exercise has shown to yield significant moderate effects on depression severity in adult patients, including the elderly. The effect diminishes when only high-quality studies are analyzed but reaches similar magnitude of other efficacious treatments. Additionally, exercise showed positive effects on sleep, cardiorespiratory fitness and quality of life in depressed patients. In children and adolescents and during the peripartum period, exercise interventions have been found have small-to-moderate effects, but studies varied in methodology and methodical quality could be improved (heterogeneous samples, blinding). Regular physical activity has been shown to have a protective effect on incident depression in adults, reducing odds by 17 to 21%. In children and adolescents, the effect tends to be smaller. Across 15 meta-analyses in samples with physical diseases, exercise-regimes have been shown to have positive effects on depressive symptoms in chronic conditions (such as pain, obesity or cardiovascular disease), cancer survivors, and in post-stroke, neurological and cardiovascular conditions, as well as in diabetes, chronic kidney disease, arthritis and HIV. Discussion: Exercise and physical activity have a wide range of benefits for depression and depressive symptoms in at-risk populations. Further research is needed to find optimal dose and duration of exercise-treatment and ways to sustainably increase physical activity in psychiatric populations and patients with chronic diseases.  Key Words:Exercise, Aerobic, Resistance, Depressive Symptoms, At-Risk Population